2022
DOI: 10.3390/cryst12060752
|View full text |Cite
|
Sign up to set email alerts
|

Variational Formulations and Isogeometric Analysis of Timoshenko–Ehrenfest Microbeam Using a Reformulated Strain Gradient Elasticity Theory

Abstract: This paper presents a novel non-classical Timoshenko–Ehrenfest beam model based on a reformulated strain gradient elasticity theory. The strain gradient effect, couple stress effect, and velocity gradient effect for vibration are included in the new model by only one material length scale parameter for each. The variational formulation and Hamilton’s principle are applied to derive the governing equations and boundary conditions. Both an analytical solution and an isogeometric analysis approach are proposed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…This study revealed that microbeams based on non-classical theories, particularly GSGET, exhibit greater stiffness than models based on classical theory. Based on (RSGET), the vibration governing equations for Timoshenko-Ehrenfest beam were acquired by [21]. The proposed analytical solution revealed a reduced deflection and a higher natural frequency in the nonclassical model utilized.…”
Section: Introductionmentioning
confidence: 99%
“…This study revealed that microbeams based on non-classical theories, particularly GSGET, exhibit greater stiffness than models based on classical theory. Based on (RSGET), the vibration governing equations for Timoshenko-Ehrenfest beam were acquired by [21]. The proposed analytical solution revealed a reduced deflection and a higher natural frequency in the nonclassical model utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the nonlocal plasticity theory, the nonlocalized variables of the material indirectly consider the changes and interactions of the internal microstructure of the material. Rawat et al [6] proposed a nonlocal plastic damage model for quasi-brittle materials in 2020 and used the method of geometric analysis [9] to avoid the problems of computational accuracy and computational efficiency that would occur during the process of finite element analysis. The application of strain gradient theory in beam bending was proposed by Li et al [7] in 2022.…”
Section: Introductionmentioning
confidence: 99%